THE INFLUENCE OF READING HABITSAND READING STRATEGIES ON STUDENTS’ READING COMPREHENSION ATJUNIOR HIGH SCHOOL 1 IN THE DISTRICT OFBENAI-KUANSING - Novri Yaldi (Journal of Education and Teaching, 2021)
The research background was caused by the low learning outcomes of students in Indonesian language subjects in grade V SD Negeri 05 Patamuan. This is due to several problems including the teacher still dominantly using conventional models, which causes students to be lazy to read and understand reading content. One way that can be used to overcome this problem is to use the Cooperative Integrated Reading and Composition (Circ) model. The purpose of this lesson is to learn to understand a passage. The approach used is a qualitative and quantitative approach using an action research design. The research design includes (1) planning, (2) implementation, (3) observation, (4) reflection. This research was conducted in 2 cycles, each cycle consisting of two meetings, the subjects studied were 27 students of class V SDN 05 Patamuan. The research instrument used in this study was the teacher activity observation sheet in the learning process, student activity sheet, student learning result sheet and documentation. The research results from each cycle carried out showed an increase in student learning outcomes. If referring to the average percentage of student learning outcomes in the form of daily tests (UH), it increased by 70.37% in cycle I and 85% in cycle II. The researcher concludes that the implementation of Indonesian language learning through the use of the Cooperative Integrated Reading and Composition (Circ) model can improve Indonesian learning outcomes for fifth grade students of SD Negeri 05 Patamuan, Patamuan sub-district.